The Effect of Tax Amnesties Programs on Tax Collection and Economic Performance: A Global Macro Economic Analysis - Mujahid, Azeem; Siddiqui, Danish Ahmed (International Journal of Social and Administrative Sciences, 2019)
Taxes are a major source of government income. Still a major part of economy exists undocumented. Tax amnesty programs are considered a short term tool to overcome tax compliance for long run benefits as well as short term recovery of revenue. This study is examined the effect of tax amnesties programs on tax revenue percentage to GDP and on macro-economic performance with the interaction of tax to GDP. Panel data of 28 years from 1990 to 2017 were collected from 24 countries and run a different test to support our results. These countries data were taken on an annual basis, where single or multiple tax amnesties launched in different years. GDP per capita, FDI per GDP, and the unemployment rate were taken as Macroeconomic variables, and the influence of tax revenue percentage to GDP in presence and absence of tax amnesty on these macroeconomic variables were tested. Results showed that the tax amnesty scheme affect GDP per capita, and FDI but not through an increase in taxes but some other reason. Successful Tax amnesty may benefit reduce the unemployment rate and improve tax to GDP in long-run with increased tax compliance is still workable. We suggest that tax authorities undertake tax reforms from successful experiences of tax amnesties in different countries for economic prosperity and better results.